Mental health effects from urban bed bug infestation (Cimex lectularius L.): a cross-sectional study. Issue 5 (25th September 2012) - Susser, Stephanie Rebecca; Perron, Stéphane; Fournier, Michel; Jacques, Louis; Denis, Geoffroy; Tessier, François; Roberge, Pasquale
Abstract : Objective: To assess whether bed bug infestation was linked to sleep disturbances and symptoms of anxiety and depression. Design: Exploratory cross-sectional study. Setting: Convenience sample of tenants recruited in apartment complexes from Montreal, Canada. Participants: 39 bed bug-exposed tenants were compared with 52 unexposed tenants. Main outcome measures: The effect of bed bug-exposed tenants on sleep disturbances, anxiety and depression symptoms measured using the Pittsburgh Sleep Quality Index, 5th subscale, Generalised Anxiety Disorder 7-item scale and Patient Health Questionnaire, 9-item, respectively. Results: In adjusted models, bed bug infestation was strongly associated with measured anxiety symptoms (OR (95% CI)=4.8 (1.5 to 14.7)) and sleep disturbance (OR (95% CI)=5.0 (1.3–18.8)). There was a trend to report more symptoms of depression in the bed bug-infested group, although this finding was not statistically significant ((OR (95% CI)=2.5(0.8 to 7.3)). Conclusions: These results suggest that individuals exposed to bed bug infestations are at risk of experiencing sleep disturbance and of developing symptoms of anxiety and possibly depression. Greater clinical awareness of this problem is needed in order for patients to receive appropriate mental healthcare. These findings highlight the need for undertaking of deeper inquiry, as well as greater collaboration between medical professionals, public health and community stakeholders.